Capital structure and corporate performance: panel evidence from oil and gas companies in Malaysia - Varian Foo; Amer Azlan Abdul Jamal; Mohd Rahimie Abdul Karim; Zatul Karamah Ahmad Baharul Ulum (2015)
The purpose of this study is to examine the relationship between capital structure and corporate performance of public listed oil and gas companies in Malaysia. For this, unbalanced panel data sets of 12 oil and gas companies were tested using panel data regression technique over the period of 2003-2013. Capital structure, the independent variable is measured by three proxies namely short-term to total debt (STDTA), long-term to total debt (LTDTA) and total debt to total asset (TTDTA). While corporate performance is measured by the company’s return on equity (ROE), return on asset (ROA) and gross margin (GM). The finding shows that capital structure is negatively related to firm’s return on equity, suggesting that an increase in the firm’s debt level would negatively affect its shareholders return. The effect of firm’s debt level with ROA and GM on the other hand, shows no impact and appears to be insignificant.